Characterization of Somatostatin Receptor Subtype 2 Expression in Stably Transfected A-427 Human Cancer Cells - Jesse J. Parry; Martin Eiblmaier; Rebecca Andrews; Laura A. Meyer; Ryuji Higashikubo; Carolyn J. Anderson; Buck E. Rogers (Molecular Imaging)
Although radiolabeled somatostatin analogs have become highly prevalent in the diagnosis and treatment of somatostatin receptor subtype (sst)-positive tumors, there are relatively few options with respect to sst-positive tumor cell lines and animal models. It would be highly beneficial, particularly for therapeutic purposes, to have several clones of one human sst2-positive cell line that express a range of sst2 concentrations for evaluating the dose response and intracellular processing of radiolabeled somatostatin analogs. The human non–small cell lung cancer line A-427 was stably transfected with a hemagglutinin-tagged human sst2. Expression of the receptor was evaluated in vitro using flow cytometry, saturation binding analysis, internalization assays, and quantitative polymerase chain reaction. The receptor expression was also validated in an in vivo mouse model in biodistribution and micro–positron emission tomography (microPET) studies using the somatostatin analog octreotide (OC), which was linked to the 64 Cu chelator 1,4,8,11-tetraazacyclotetradecane-1,4,8,11-tetraacetic acid (TETA), or 64 Cu-TETA-OC. Stable clones were isolated, and four clones (2, 4, 5, and 7) were chosen for further examination. In vitro assays showed that clone 4 had no expression of sst2, whereas the others had various levels in the order of 7 > 2 > 5. Biodistribution studies with 64 Cu-TETA-OC showed the same rank order, with tumor uptake of the clones ranging from 0.8 to 6.5% injected dose/g. These studies showed that there was a strong correlation among the in vitro assays and between the in vitro assays and the biodistribution. MicroPET confirmed significant uptake of 64 Cu-TETA-OC in clone 7 and background uptake in clone 4. These studies show that clones of a human cell line can be produced expressing various levels of sst2 that should be useful for the future evaluation of radiolabeled somatostatin analogs.